The Role of Bank and Corporate Balance Sheets on Early Warning Systems of Currency Crises—An Empirical Study - Mulder, Christian; Perrelli, Roberto; Duarte Rocha, Manuel (Taylor and Francis, 2016)
This study analyzes the role of bank and corporate balance sheets on early warning systems (EWS) of currency crises. Using firm-level data on debt structure, leverage, liquidity, and profitability, this study presents estimations of EWS for a panel of emerging markets. Using calibration experiments, we assess the performance of alternative EWS specifications in a comprehensive range of crisis-probability cut-offs‏. These models supplement EWS based on traditional macroeconomic indicators, improving forecasting performance substantially. The results support the third-generation models of currency crises and can assist policymakers on the design of surveillance strategies tailored for heterogeneous levels of risk tolerance and country specificities.